Análisis financiero a los balances contables de Andrés Felipe Minga García de la provincia del Azuay, cantón Cuenca del periodo 2014-2015 - García Andrade, Nancy Cecilia (2017)
he present research work titled "Financial Analysis of Andrés Felipe Minga Garcia of the province of Azuay, Cuenca, from the period 2014-2015.", was developed as a prerequisite to obtaining the degree of Accounting and Auditing Auditor Public Auditor, at the National University of Loja. The research is structure in accordance with the graduation norms established in the Regulation of Academic Regime of the National University of Loja. The present work is aimed at providing a contribution to the business of the professional Andrés Minga, being the same one company, starting with the collection regarding the theoretical contents on financial statements, financial analysis with its respective classification vertical, horizontal analysis, financial indicators of Liquidity, Solvency and Profitability, which allowed to measure the profitability and operational and financial structure of the construction company. With the horizontal and vertical analysis was concluded that the company has high own capital and that the profits obtained do not represent a good financial profitability for the company. The report allows the professional to have a valid instrument, for an effective and timely decision making, establishing a future projection of their business. Once the research is carried out, it presents the conclusions and recommendations of the work done, which will serve as a guide for the professional.